2020
DOI: 10.25287/ohuiibf.702681
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of The Quality of Audit on The Financial Performance of Companies: An Application in Borsa Istanbul

Abstract: Bağımsız denetim, firmaların hazırlamış olduğu finansal tabloların firma dışı üçüncü kişiler tarafından denetlenmesi ve elde edilen sonuçların raporlanmasıdır. Bağımsız denetimin daha kaliteli olduğu piyasalarda sağlanacak güven ortamı, beraberinde yatırımcılar, kreditörler ve potansiyel ortaklar gibi farklı finansal tablo kullanıcılarının daha sağlıklı kararlar vererek sağlam adımlar atmasını sağlayacaktır. Bu çalışmanın amacı bağımsız denetim kalitesinin firmaların finansal performansı üzerinde etkili olup o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…In the literature, similar results were found on companies active in different areas. Analysis results support the findings of Cengiz, Dinç, and Güngör (2017), Kesen andSalur (2020), andBouaziz (2012). Banks that know they would have a quality audit process spare their procedures to maximize and/or optimize their profitability while conducting the same according to legal regulations in effect.…”
Section: Extended Abstractsupporting
confidence: 85%
“…In the literature, similar results were found on companies active in different areas. Analysis results support the findings of Cengiz, Dinç, and Güngör (2017), Kesen andSalur (2020), andBouaziz (2012). Banks that know they would have a quality audit process spare their procedures to maximize and/or optimize their profitability while conducting the same according to legal regulations in effect.…”
Section: Extended Abstractsupporting
confidence: 85%
“…In the study, it was concluded that there was a significant and positive relationship between independent audit quality and financial performance. Kesen and Salur (2020) investigated in their study whether the quality of independent audit had an impact on the financial performance of firms. For this purpose, they analyzed the financial statements of 148 companies traded in the BIST manufacturing sector between 2013 and 2018 and applied multiple linear regression…”
Section: Literature Reviewmentioning
confidence: 99%